2019
DOI: 10.1042/bsr20190110
|View full text |Cite
|
Sign up to set email alerts
|

Association between interleukin-21 gene rs6822844 polymorphism and rheumatoid arthritis susceptibility

Abstract: Controversial results concerning the association between a polymorphism rs6822844 in the interleukin (IL) 21 (IL-21) gene and rheumatoid arthritis (RA) have existed. A meta-analysis to confirm above relationships is necessary to be performed immediately. We conducted a search in the PubMed database, covering all papers published up to 20 October 2018. Overall, six case–control studies with 3244 cases and 3431 healthy controls were included. Odds ratios (ORs) and 95% confidence intervals (CIs) were used to asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 43 publications
(39 reference statements)
1
5
0
Order By: Relevance
“…A study conducted on a cohort of Iraqi individuals discovered that the GG genotype/G allele of IL-21 (rs2055979) may be related to a tendency to multiple sclerosis (15) . In our results, there was no significant association as regards ESR, CRP, and RF with IL-21 genotypes in the RA group, similar to another study (7) that found; the analysis of ESR, CRP and RF with the IL-21 and IL-21R polymorphisms did not show differences between the variant genotypes.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…A study conducted on a cohort of Iraqi individuals discovered that the GG genotype/G allele of IL-21 (rs2055979) may be related to a tendency to multiple sclerosis (15) . In our results, there was no significant association as regards ESR, CRP, and RF with IL-21 genotypes in the RA group, similar to another study (7) that found; the analysis of ESR, CRP and RF with the IL-21 and IL-21R polymorphisms did not show differences between the variant genotypes.…”
Section: Discussionsupporting
confidence: 90%
“…In the pathogenesis of RA, inflammatory cytokines play an important role in inducing the inflammatory response and releasing other inflammatory mediators (11) . One of these cytokines is IL-21, which has various effects on the immune system and plays an essential role in the proliferation of B cells, differentiation of plasma cells, and immunoglobulin synthesis; therefore, the effects of IL-21 on B cells may take part in the development of different autoimmune disorders (7,8) . In recent years, IL-21 has played a vital role in the pathogenesis and progression of RA (12) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, these variables must be examined in subsequent articles, regardless of the difficulties in assessing environmental exposures and study design. 22,23 Some limitations exist in our meta-analysis. To begin with, we only enrolled researches in Chinese and English, thus, some potentially eligible researches published in other languages might be omitted.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these variables must be examined in subsequent articles, regardless of the difficulties in assessing environmental exposures and study design. 22 , 23 …”
Section: Discussionmentioning
confidence: 99%